INTEGRATING CYBERSECURITY INTO INTERNAL AUDIT THROUGH A SELF-ASSESSMENT TOOL BASED ON A SYSTEMATIC LITERATURE REVIEW - Cernovschi, Cristina-Raluca; Ciubotariu, Marius-Sorin; Mihaila, Svetlana (Economy and Sociology, 2025)
In an era in which technological innovations are reshaping organizations’ operational strategies, bringing with them new challenges related to data protection and privacy, internal auditing is compelled to expand its scope to incorporate the risks associated with cybersecurity. In this context, we propose a systematic review of 16 studies indexed in the Web of Science database covering the period 2017-2025, selected by clear inclusion and exclusion criteria, based on capturing the interdependence between the internal audit function and the cybersecurity of an enterprise to assess the contribution of internal auditors to mitigate cyber risks. The results take the form of a categorization of the available studies according to the ideas addressed by the authors, as also a company-level self-assessment form on the integration of cybersecurity into the internal audit process. These results are of twofold relevance, firstly they serve academics who can more easily track the main interests in this area as well as the existing gaps in the literature, and secondly they help companies to diagnose the maturity status of integrating cybersecurity into internal audit processes. However, these results are limited by the analysis of a small number of studies, as restricted access to some articles prevented their inclusion in the analysis.